Comparative study of DIPSI and IADPSG criteria for diagnosis of GDM - Srinivasan, Swathy; Reddi, Rani P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
GDM is defined as any degree of glucose intolerance with onset or first recognition during pregnancy. The prevalence of GDM varies, widely based on the diagnostic criteria used and the ethnic group studied. It is associated with adverse maternal and perinatal outcome. Incidence of GDM in India is 1-14%. There are several screening and diagnostic tests for GDM. It is important to diagnose early and treat to prevent these complications. The present study was done to compare Diabetes in Pregnancy Study Group India (DIPSI) with International Association of the Diabetes and Pregnancy Study Groups (IADPSG) criteria for diagnosis of GDM and to assess the validity of these methods. Methods: It was a cross sectional study done in 144 pregnant women who fulfilled the inclusion criteria. They underwent non - fasting OGTT with 75 grams glucose which was given irrespective of the last meal. A venous blood sample was drawn two hours after glucose administration. They were advised to come two to three days later and repeated with 75 grams OGTT after an overnight fast of atleast 8 hours. Venous blood sample was drawn at fasting, one hour and two hours after load with 75 grams of glucose. Plasma glucose was measured by using an autoanalyzer by glucose - oxidase peroxidase (GOD - POD) technique. Results: The epidemiological parameters like Age, BMI, Parity and Gestational age did not have any difference between two groups. 17.4% was diagnosed by DIPSI criteria and 15.3% was diagnosed by IADPSG criteria and 6.9% was diagnosed by both. Sensitivity and specificity of DIPSI was 45% and87% and sensitivity and specificity of IADPSG was 40% and89% respectively. According to kappa statistics, the p-value is 0.000. Conclusions: In present study it was concluded that screening is very essential in all pregnant women due to high prevalence of GDM in India. By comparing these two criteria, sensitivity of DIPSI was found better than IADPSG criteria in diagnosing GDM. Though IADPSG is universally accepted for diagnosis, DIPSI has still got a place in low resource countries as it is easy, cost effective and non fasting test.